2015
DOI: 10.1080/19443994.2013.860628
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of anaerobic fluidized bed reactors using brick beads and porous ceramics as support materials for treating terephthalic acid wastewater

Abstract: A B S T R A C TThis study evaluated two different porous support materials (brick beads and porous ceramics) used in rapid mass-transfer anaerobic fluidized bed reactors (AFBRs) for treating terephthalic acid wastewater. The AFBRs, denoted as R1 (containing brick beads) and R2 (containing porous ceramics), were inoculated with anaerobic sludge. Results showed that the system organic loading rate increased from 7.37 kg COD/(m 3 d) to 18.52 kg COD/(m 3 d) over a period of 73 d. During the steady period, R2 showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The surface topography of the brick was analyzed by SEM, as shown in Figure 2. It was observed that the surfaces of lime sand bricks were uneven with large numbers of pore spaces, which perhaps provided sites for adsorption of Cu(II) either physically or chemically [23]. Figure 3 shows the FTIR spectra of the lime sand brick before Cu(II) adsorption.…”
Section: Characterization Of the Lime Sand Bricksmentioning
confidence: 99%
“…The surface topography of the brick was analyzed by SEM, as shown in Figure 2. It was observed that the surfaces of lime sand bricks were uneven with large numbers of pore spaces, which perhaps provided sites for adsorption of Cu(II) either physically or chemically [23]. Figure 3 shows the FTIR spectra of the lime sand brick before Cu(II) adsorption.…”
Section: Characterization Of the Lime Sand Bricksmentioning
confidence: 99%
“…The fluidized-bed bioreactor (FBBR) has attracted significant attention as an alternative to the conventional suspended-growth wastewater-treatment processes because of its high-efficiency performance. Several advantages of FBBR compared with conventional wastewater-treatment processes, such as its higher biomass concentration, higher mass-transfer efficiency, lower hydraulic-retention time (HRT), and smaller footprint, have been discussed extensively in the literature. Compared with the conventional liquid–solid FBBR, the liquid–solid circulating-fluidized-bed bioreactor (CFBBR) has additional advantages . The liquid–solid CFBBR integrates two fluidized beds into one unit, and several biochemical processes can occur within a single system, with particle recirculation between the two fluidized beds.…”
Section: Introductionmentioning
confidence: 99%